The Role of Light-Harvesting Complex II Organization in the Efficiency of Light-Dependent Reactions in the Photosynthetic Apparatus of Pisum sativum L. - Georgi D. Rashkov; Martin A. Stefanov; Amarendra N. Misra; Emilia L. Apostolova (Plants, 2025)
In this study, the functions of the photosynthetic machinery were evaluated using chlorophyll a fluorescence technique (PAM and JIP test) in pea plants (Pisum sativum L. cv Borec) and its LHC II oligomerization variants (mutants Costata 2/133 and Coeruleovireus 2/16). The oligomeric forms of LHCII increased in the following order: Costata 2/133 < Borec wt < Coeruleovireus 2/16. Data revealed that the mutant with higher LHCII oligomerization (Coeruleovireus 2/16) at low light intensity (LL, 150 µmol photons/m2·s) exhibited the following: (i) decreased energy dissipation and increased electron transport efficiency; (ii) higher reaction center density; (iii) increased amounts of the open reaction centers (qp) and their excitation efficiency (Φexc); and (iv) influenced the reoxidation of QA−, alleviating its interaction with plastoquinone. These effects enhanced photosynthetic performance related to PSII photochemistry (PIABS) and overall photosynthetic efficiency (PItotal). High light intensity (HL, 500 µmol photons/m2·s) caused a reduction in open reaction centers (qp), excitation efficiency (Φexc), photochemical energy conversion of PSII (ΦPSII), maximum efficiency of PSII photochemistry in light (Fv′/Fm′), and linear electron transport via PSII, with more pronounced effects observed in membranes with a lower degree of LHCII oligomerization (Costata 2/133). This study provides novel experimental evidence for the pivotal role of the LHCII structural organization in determining the efficiency of light-dependent reactions of photosynthesis.